2007
DOI: 10.1021/la063180k
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Surface Modification and Characterization of POSS-Based Nanocomposite Polymeric Thin Films

Abstract: The effect of a remote oxygen plasma on nanocomposite hybrid polymer thin films of poly[(propylmethacryl-heptaisobutyl-polyhedral oligomeric silsequioxane)-co-(methylmethacrylate)] (POSS-MA) has been examined by advancing contact angle, X-ray photoelectron spectroscopy (XPS), and variable-angle spectroscopic ellipsometry (VASE). Exposure to a 25 W remote oxygen-containing plasma was found to convert the surface of POSS-MA films from hydrophobic to hydrophilic within 20 s. The exposure time needed for this conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Indeed, ATR-FTIR analysis identified key chemical species on plasmatreated films where the major difference between samples was the appearance of CO, Si O Si , OH, and silanol ( SiOH) groups, confirming the presence of POSS within the polymeric matrix. This was supported by work of Augustine et al [50] using high-resolution X-ray photoelectron spectroscopy analysis of nanocomposite films after PSM. It was found that after treatment with reactive O 2 , energetic particles removed the isobutyl side chain groups from the POSS nanoparticles and replaced them with O 2 to form SiO 2 (silica) like structures, which became further resistant to oxidation during treatment [50].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Indeed, ATR-FTIR analysis identified key chemical species on plasmatreated films where the major difference between samples was the appearance of CO, Si O Si , OH, and silanol ( SiOH) groups, confirming the presence of POSS within the polymeric matrix. This was supported by work of Augustine et al [50] using high-resolution X-ray photoelectron spectroscopy analysis of nanocomposite films after PSM. It was found that after treatment with reactive O 2 , energetic particles removed the isobutyl side chain groups from the POSS nanoparticles and replaced them with O 2 to form SiO 2 (silica) like structures, which became further resistant to oxidation during treatment [50].…”
Section: Discussionmentioning
confidence: 65%
“…This was supported by work of Augustine et al [50] using high-resolution X-ray photoelectron spectroscopy analysis of nanocomposite films after PSM. It was found that after treatment with reactive O 2 , energetic particles removed the isobutyl side chain groups from the POSS nanoparticles and replaced them with O 2 to form SiO 2 (silica) like structures, which became further resistant to oxidation during treatment [50]. A slight decrease in transmission was observed in the ATR-FTIR spectra for plasma-treated nanocomposite films with increasing power output, particularly in the O CO O and Si O Si band regions of the spectra.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Polyhedral oligomeric silsesquioxane (POSS) molecules were deposited on polyimide film surfaces and exposure to radio frequency-generated oxygen plasma caused changes in both chemistry and topography ( Figure 1A and B). 23 POSS molecules have been demonstrated to form passivating silica-type coatings on surfaces exposed to atomic oxygen, [24][25][26] and this system was selected for investigation as a passive dust mitigation surface with the anticipation that the surface could be modified in a low Earth orbit (LEO) en route to the lunar surface. Formation of a POSS sub-monolayer resulted in reduced surface energy as evidenced by water contact angle goniometry measurements ( Figure 1C), suggesting reduced particle adhesion.…”
Section: A "Lotus Effect" and Poss Spray Depositionmentioning
confidence: 99%
“…Due to its special cubic cage structure, it is a useful nanometer-scale building block in many polymeric materials and nanocomposites, to improve the performance of the materials [32][33][34][35][36]. Since the structure of the organometallic precursors could badly affect the morphology and properties of the yielded magnetic materials, thus, it is an effective approach to improve the performance of the obtained magnetic materials by adjusting the structure of the organometallic precursors.…”
Section: Introductionmentioning
confidence: 99%